Implementation of Interactive Media using Padlet Integrated with Educaplay Platform on IPS Subject - Annisa Laila Dharmawan; I Nyoman Ruja (JURNAL PENDIDIKAN IPS, 2025)
Digital learning media is learning that aligns with current developments at this time. The Platform utilized for this purpose is padlet. Padlet is a web based application that allows users to create virtual walls where students can upload text, images, links, and videos in one collaborative space. This Platform is integrated with Educaplay as a final assessment. Both Platforms of which produce interactive learning experiences. This aims to increase student engagement in the classroom. This study employes a qualitative approach method. Specifically a descriptive method. The research was conducted at SMP 14 Malang, with a focus on students from class 7.4. Data collection using 3 techniques: observation, interviews and documentation. The findings of this study indicate that use of Padlet media integrated with Educaplay can increase student interactivity in the classroom. The use of the Froggy Jumps game in Educaplay has succeeded in attracting students attention and motivation, making the learning process more fun and challenging. In addition to making learning more enjoyable, this integration positively contributes to the development of 21st-century skills such as decision-making, critical thinking, and collaboration.